Long term Educational Public Funding in Costa Rica (1860-2016) - Molina Jiménez, Iván (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The present article analyzes the funding of State education in Costa Rica on the long term. With this purpose, the indings and limitations of previous studies on educational funding were explored. In consequence, the principal tendencies of growth or decline of inancing were identiied, including their relation to processes of economic crisis, coups d´etat, wars and expansion cycles of export and internal market activities. Finally, the impact of the increase or decrease of educational funding on primary, secundary and university education coverage was analyzed. It is concluded that, from the XIX century, the Costa Rican State has maintained a solid and growing commitment with the inancing of its public education system, with some (usually short-lasting) regressions, except for the period from 1981 to 2007.